Healthy physical education curriculum model and students' extracurricular sports participation --test based on the trans-contextual model of motivation - Xiaoliang Hao; Yunyun Yang (BMC, 2022)
Abstract Background In recent years, the mental health level and physical activity level of Chinese teenagers are not ideal, and all sectors of society are actively reversing this bad situation. The purpose of this study is to test the influence of healthy physical education curriculum model on middle school students' extracurricular sports participation based on the trans-contextual model of motivation (TCM). Methods The trial adopts quasi-experimental design comparing equivalent groups. The experimental group adopted the healthy physical education curriculum model in physical education (PE), and the control group adopted the technical-traditional teaching. During the 12 weeks intervention, 327 junior school freshmen completed the test of TCM variables four times as the pre-test, test 2, test 3 and post-test of this experimental study. Results After the intervention, students' perceived need support in PE, autonomous motivation in PE, autonomous motivation in leisure time (LT)and the amount of extracurricular sports activities in the experimental group have increased significantly. The perceived need support of experimental group students can predict autonomous motivation in PE positively (β = 0.385, P<.001); Autonomous motivation in PE can predict autonomous motivation in LT positively (β = 0.462, P<.001); Autonomous motivation in LT can predict the intention of extracurricular sports participation positively, and the direct effect was significant (β = 0.172, P<.01), the total indirect effect was significant (β = 0.382, P<.001), the indirect effect of subjective norms was not significant (P>.05); Extracurricular sports participation intention can predict the amount of extracurricular sports activities positively (β = 0.327, P<.001). Conclusions The structural characteristics of healthy physical education curriculum model provide need support for students' learning, improve students' autonomous motivation in and out of PE, and finally promote students' participation in extracurricular sports.